3 - Why the African Union Should be Dismantled and Buried with Gaddafi - Sangmpam, S.N. (Africa Development, 2018)
One enduring project of pan-Africanists is an all-Africa union as the solution to Africa’s socio-economic predicament. They view the lack of such a union as one of the major causes of the predicament. From Nkrumah to the African Union (AU) passing by the Organization of African Unity (OAU), their disagreements have been about the means and ways of achieving this goal. In their view, the development of sub-Saharan Africa (SSA) is inseparable from that of North Africa. I argue that this is not and should not be the case, because SSA socio-economic outcomes and their causes diverge organically from those of North Africa. As the institutional symbol of this pan-African view, the AU should be dismantled. SSA should be allowed to reconstitute itself, without North Africa, into a self-sustaining, organically integrated Unifederation that can finally address and solve its predicament. Gaddafi’s demise allows SSA to do so.